Social and economic determinants of Turkish voter choice in the 1995 parliamentary election - Ali T. Akarca; Aysit Tansel (Institute for the Study of Labor (IZA), 2007)
1995 Turkish parliamentary election was held almost under the conditions of a controlled experiment. The unique cross-section data pertaining to this election is utilized to study the voter behavior in Turkey. Turkish voters are found to take government's economic performance into account but not look back beyond one year. A poor performance is found to benefit the extremist opposition parties at the expense of the major incumbent party. The minor incumbent and the centrist opposition parties appear to be unaffected by economic conditions. Voters also exhibit a tendency to vote against the parties holding power. The party preferences of Turkish voters depend on their socioeconomic characteristics as well.
Keywords: 330; Wahlverhalten; Wirtschaftslage; Türkei